1975
DOI: 10.1002/macp.1975.021760615
|View full text |Cite
|
Sign up to set email alerts
|

Polymerisationen und polymerisationsinitiatoren, 16. Einfluß von Thioxo‐Gruppen in barbitursäurederivaten auf die polymerisationsauslösung von methacrylsäure‐methylester

Abstract: 5‐Alkyl‐1,3‐dimethylbarbitursäuren lösen in Gegenwart von Cu2+, Cl− und Luftsauerstoff die radikalische Polymerisation von Methacrylsäuremethylester aus. Die Initiatorwirkung wi+d durch Thioxo‐Gruppen in 2‐Stellung etwas verstärkt, in 4‐ bzw. 4,6‐Stellung dagegen stark vermindert. Die Wirkung dieser 4‐ bzw. 4,6‐Thioxobarbitursäuren als Inhibitoren beruht auf der Stabilisierung der primär gebildeten Radikale durch die benachbarten Thioxo‐Gruppen, wodurch Weiterreaktion am S‐Atom unter Dimerisierung zu Disulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In an attempt to avoid the formation of CTCs in acidic circumstances, Bredereck et al have suggested that materials containing alternative coinitiators instead of basic amines would present better color stability and mechanical properties . Since then, some studies have employed the barbituric acid derivatives (BADs) as amine substitutes to the coinitiation of the polymerization reaction . Nevertheless, the most part of these studies has evaluated the influence of the BADs exclusively in the chemical polymerization of experimental materials.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to avoid the formation of CTCs in acidic circumstances, Bredereck et al have suggested that materials containing alternative coinitiators instead of basic amines would present better color stability and mechanical properties . Since then, some studies have employed the barbituric acid derivatives (BADs) as amine substitutes to the coinitiation of the polymerization reaction . Nevertheless, the most part of these studies has evaluated the influence of the BADs exclusively in the chemical polymerization of experimental materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to generate free radical for initiating polymerization, a reaction between 1,3,5‐trimethylbarbituric acid (TMBA) and copper‐ion or chloride‐ion has been applied 1–30. Thus, TMBA generates highly concentrated free radical and accelerates polymerization 31–40…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TMBA generates highly concentrated free radical and accelerates polymerization. [31][32][33][34][35][36][37][38][39][40] The storage stability of TMBA, however, is extremely low due to its highly oxidizable nature as described earlier. Furthermore, when TMBA is used to prepare a biological hard tissue-adhesive material, TMBA with deliquescence easily agglomerates and induces aggregation between coexisting components such as polymer beads, leading to considerable difficulty in the handling operation.…”
Section: Introductionmentioning
confidence: 99%